Speaker tracking in reverberant environments using multiple detections of arrival - Evers,C; Rafaely,B; Naylor,PA (IEEE, 2017)
Accurate estimation of the Direction of Arrival (DOA) of a soundsource is an important prerequisite for a wide range of acoustic sig-nal processing applications. However, in enclosed environments,early reflections and late reverberation often lead to localization er-rors. Recent work demonstrated that improved robustness againstreverberation can be achieved by clustering only the DOAs fromdirect-path bins in the short-term Fourier transform of a speech sig-nal of several seconds duration from a static talker. Nevertheless, formoving talkers, short blocks of at most several hundred millisecondsare required to capture the spatio-temporal variation of the sourcedirection. Processing of short blocks of data in reverberant envi-ronment can lead to clusters whose centroids correspond to spuri-ous DOAs away from the source direction. We therefore propose inthis paper a novel multi-detection source tracking approach that es-timates the smoothed trajectory of the source DOAs. Results for re-alistic room simulations validate the proposed approach and demon-strate significant improvements in estimation accuracy compared tosingle-detection tracking.